2020
DOI: 10.1029/2019sw002427
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Asymmetries in the Ground Magnetic Response to Interplanetary Shocks: The Role of Shock Impact Angle

Abstract: Interplanetary (IP) shocks drive magnetosphere‐ionosphere (MI) current systems that in turn are associated with ground magnetic perturbations. Recent work has shown that IP shock impact angle plays a significant role in controlling the subsequent geomagnetic activity and magnetic perturbations; for example, highly inclined shocks drive asymmetric MI responses due to interhemispherical asymmetric magnetospheric compressions, while almost head‐on shocks drive more symmetric MI responses. However, there are few o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…Numerical simulations show that shocks with small impact angles usually lead the MI system to faster and stronger responses in comparison to shocks with large impact angles (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov et al, 2015). These results have been confirmed by many experimental studies as well (Oliveira & Raeder, 2015;Oliveira, Arel, et al, 2018;Rudd et al, 2019;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006;Xu et al, 2020). Oliveira and Raeder (2014) studied the effects caused by shock orientations on the Earth's magnetosphere through numerical simulations.…”
Section: 1029/2020gl090857mentioning
confidence: 83%
See 2 more Smart Citations
“…Numerical simulations show that shocks with small impact angles usually lead the MI system to faster and stronger responses in comparison to shocks with large impact angles (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov et al, 2015). These results have been confirmed by many experimental studies as well (Oliveira & Raeder, 2015;Oliveira, Arel, et al, 2018;Rudd et al, 2019;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006;Xu et al, 2020). Oliveira and Raeder (2014) studied the effects caused by shock orientations on the Earth's magnetosphere through numerical simulations.…”
Section: 1029/2020gl090857mentioning
confidence: 83%
“…With the shock normal vector given by truen=false(nx,ny,nzfalse) in geocentric solar ecliptic (GSE) coordinates and truen=false(nx, ny, nz) in solar magnetic (SM) coordinates, we compute the following: θxn=cos1false(nxfalse), φyn=tan1()nzny, θdn=tan1()nznx2+ny2, where θxn is the angle the shock normal performs with the Sun‐Earth line, φyn is the angle the normal vector performs with the y axis in the yz plane, and θdn is the angle between the shock normal vector and the SM xy plane (Xu et al, 2020). The SM angle ( θdn) is slightly more inclined than the GSE angle ( …”
Section: Shock Parameter Computations and Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…All panels in Figure 2 indicate positive jumps in the IMF and plasma parameter magnitudes (velocity, number density, and temperature), which are fast forward shock signatures (Priest, 1981;Oliveira, 2017). Additionally, the HIS shows more variability in the y and z components of the IMF and solar wind speed due to its normal inclinations with respect to the xy and xz planes (Xu et al, 2020). Table 2 also shows that the average southward component of the IMF (B z2 ) was slightly more negative in the downstream region of the HIS (-14 nT) than in the downstream region of the NFS (-12 nT).…”
Section: Conditions For Event Selectionmentioning
confidence: 95%
“…Consequently, when shocks hit Earth, different levels of geomagnetic activity may follow, including ground sudden impulses, field-aligned current and auroral intensifications, and wave response in the magnetosphere-ionosphere system (e.g., see review by Oliveira & Samsonov, 2018). Observations and simulations show that geomagnetic activity following the impact of an inclined shock is usually weaker and slower than the geomagnetic activity following a frontal shock as a result of asymmetric magnetospheric compressions (Takeuchi et al, 2002;Guo et al, 2005;Grib & Pushkar, 2006;Wang et al, 2006;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017;Shi et al, 2019;Xu et al, 2020). Numerical simulations conducted by Oliveira and Raeder (2014) showed that a frontal shock triggered intense substorm activity, whereas an inclined shock triggered moderate substorm activity, even though the inclined shock was stronger.…”
Section: Introductionmentioning
confidence: 99%